Multiscale drivers of carabid beetle (Coleoptera: Carabidae) assemblages in small European woodlands. Issue 1 (7th November 2020) - Marrec, Ronan; Le Roux, Vincent; Martin, Ludmilla; Lenoir, Jonathan; Brunet, Jörg; Cousins, Sara A. O.; De Smedt, Pallieter; Deconchat, Marc; Diekmann, Martin; Ehrmann, Steffen; Gallet‐Moron, Emilie; Giffard, Brice; et al.
Abstract: Aim: The spatio‐temporal connectivity of forest patches in lowland agricultural landscapes and their age matter to explain current biodiversity patterns across regional as well as biogeographical extents, to the point that their effect exceeds the one of macroclimate for plant diversity in the understorey of temperate forests. Whether this remains true for other taxonomic groups is still largely unknown. Yet, this relative influence has important consequences for ecosystem functioning and the delivery of ecosystem services. Focusing on carabid beetle assemblages, we assessed the relative importance of macroclimatic, landscape and patch attributes in driving local species richness (α‐diversity) and species dissimilarity between patches (β‐diversity). Location: Deciduous forest patches in seven regions along a 2, 100‐km‐long latitudinal gradient across the European temperate forest biome, from southern France to central Sweden. Methods: We sampled 221 forest patches in two 5‐km × 5‐km landscape windows with contrasting management intensities. Carabid beetles were classified into four habitat‐preference guilds: forest‐specialist, forest‐generalist, eurytopic and open‐habitat species. We quantified the multi‐level environmental influence using mixed‐effects models and variation partitioning analysis. Results: We found that both α‐ and β‐diversity were primarily determined by macroclimate, acting as a large‐scale ecological filter on carabid assemblages among regions. Forest‐patch conditions, including biotic and abiotic heterogeneity as well as patch age (but not patch size), increased α‐diversity of forest species. Landscape management intensity weakly influenced α‐diversity of forest species, but increased the number of non‐forest species in forest patches. Beta diversity of non‐forest species increased with patch heterogeneity and decreased with landscape management intensity. Main conclusions: Our results highlight the leading role of broad macroclimatic gradients over local and landscape factors in determining the composition of local carabid communities, thereby shedding light on macroecological patterns of arthropod assemblages. This study emphasizes the urgent need for preserving ancient forest patches embedded in agricultural landscapes, even the small and weakly connected ones.